Development of Canva-Based Interactive Learning Media for Mixed Fractions in Elementary School - Cecep Kurniawan; Sahrun Nisa; M. Habibi; Adrias; Masniladevi (Universitas Negeri Malang, 2026)
Abstract: The development of interactive learning media is crucial in elementary mathematics education, as abstract concepts often challenge students’ comprehension. This study focused on creating Canva-based interactive learning media for mixed-fraction topics that met validity, practicality, and effectiveness criteria. The ADDIE model was implemented in three elementary schools. The results showed that the media validation score increased significantly from 58% to 93.9%. Teacher and student response rates were also very high, reaching 94% and 91.5%, respectively. Furthermore, student learning outcomes improved significantly from an average score of 33.84285 to 86.592885 with an N-Gain score of 0,8041009763 categorized as high. These findings indicate that Canva-based interactive learning media are highly valid, practical, and effective for mathematics instruction. In addition, the integration of visual elements, animations, and interactive features enhances student engagement and helps them better visualize complex concepts such as mixed fractions. The use of technology-based media also supports student-centered learning and increases active participation. Overall, Canva demonstrates strong potential as an innovative tool to improve learning outcomes and conceptual understanding among elementary school students. Abstrak: Pengembangan media pembelajaran interaktif sangat penting dalam pendidikan matematika sekolah dasar, karena konsep-konsep abstrak seringkali menyulitkan pemahaman siswa. Penelitian ini berfokus pada pembuatan media pembelajaran interaktif berbasis Canva untuk topik pecahan campuran yang memenuhi kriteria validitas, kepraktisan, dan efektivitas. Model ADDIE diterapkan di tiga sekolah dasar. Hasil penelitian menunjukkan bahwa skor validasi media meningkat secara signifikan dari 58% menjadi 93,9%. Tingkat respons guru dan siswa juga sangat tinggi, masing-masing mencapai 94% dan 91,5%. Selain itu, hasil belajar siswa meningkat secara signifikan dari skor rata-rata 33,84285 menjadi 86,592885 dengan skor N-Gain sebesar 0,8041009763 yang dikategorikan sebagai tinggi. Temuan ini menunjukkan bahwa media pembelajaran interaktif berbasis Canva sangat valid, praktis, dan efektif untuk pengajaran matematika. Selain itu, integrasi elemen visual, animasi, dan fitur interaktif meningkatkan keterlibatan siswa serta membantu mereka memvisualisasikan konsep-konsep rumit seperti pecahan campuran dengan lebih baik. Penggunaan media berbasis teknologi juga mendukung pembelajaran yang berpusat pada siswa dan meningkatkan partisipasi aktif mereka. Secara keseluruhan, Canva menunjukkan potensi yang besar sebagai alat inovatif untuk meningkatkan hasil belajar dan pemahaman konseptual di kalangan siswa sekolah dasar.